Evaluation of endothelial protein C receptor in patients with systemic lupus erythematosus: correlation with disease activity and lupus nephritis - Asmaa Shaaban (Egyptian Rheumatology and Rehabilitation, 2015)
Introduction Systemic lupus erythematous (SLE) is a systemic, multifaceted inflammatory disease with clinical manifestations is protean and follows a relapsing and remitting course. Lupus Nephritis (LN) is one of the most frequent and serious manifestation. Endothelial protein C receptor (EPCR) is a transmembrane receptor that is shed into soluble form (sEPCR) in inflammatory status. It is demonstrated as a part of the pathobiology of the SLE disease. Aim of the work To assess correlation of sEPCR level in SLE patients to the disease activity in these patients and to relate sEPCR to LN. Patients and methods Serum level of sEPCR using enzyme-linked immunosorbent assay (ELISA), chemical and immunological markers of SLE were measured in 30 SLE patients and 30 age and sex matched apparently healthy controls. SLE patients were subgrouped into 20 patients without LN and 10 with LN. Disease activity was assessed using SLE Disease Activity Index (SLEDAI). Results A significantly higher sEPCR level was found on comparing SLE patients to controls with statistically highly significant difference (z = 4.8, P < 0.001). Moreover, there was a significantly higher sEPCR level on comparing SLE patients with LN to those without LN with statistically highly significant difference (z = 3.9, P < 0.001). Serum sEPCR had a highly significant positive correlation with SLEDAI in SLE patients (r = 0.66, P < 0.01). Conclusion sEPCR has a possible role in the pathogenesis of SLE and particularly LN diseases, reflecting disease activity in SLE patients.